The effect of linoleic acid on the growth and vascularity of L-1 Sarcoma in mice and on the cutaneous angiogenesis induced by tumour cells - Białas, Beata; Skopińska-Różewska, Ewa; Sommer, Ewa; Skurzak, Henryk; Filewska, Małgorzata; Sommer, Sylwester (Contemporary Oncology/Współczesna Onkologia, 2001)
Linoleic acid (LA) is an essential, dietary polyunsaturated n-6 fatty acid (PUFA), that is metabolised in the body by way of intermediate products to arachidonic acid, the precursor of two families of eicosanoids formed from cyclooxygenase- and lipoxygenase-mediated reactions. Fatty acids carry out many functions that are necessary for normal physiological function and good health. LA is present in large amounts in corn, sunflower, soy and evening primrose oils. Some recent epidemiological and clear experimental data now linked a high dietary intake of n-6 PUFAs, such as LA to increased risk for cancer of breast, colon and prostate. The precise mechanism of LA action on tumourigenesis is not clear. In our previous study we observed enhancing effect of evening primrose oil, which consists of 70% LA and 10% gamma linolenic acid (GLA) on cutaneous angiogenesis induced in mice after grafting tumour cells of various origin. Aim: The object of the present study was to evaluate the influence of LA on cutaneous angiogenesis induced in Balb/c mice by syngeneic sarcoma L-1 cells, and on the growth and vascularization of this tumour. Material and methods: Mouse L-1 Sarcoma cells were grafted intradermally into Balb/c mice, fed subsequently LA dissolved in 0,2 % ethyl alcohol, in dose 3,5 mg per mouse/day, for 3 days. Three days after the cells grafting mice were sacrificed and newly formed blood vessels were counted in dissection microscope. The other groups of mice who were subcutaneusly injected with 106 Sarcoma cells were fed LA for 14 days using daily doses as indicated above, or 0,2% ethyl alcohol (controls). After 14 days mice were killed, tumors were excised, weighted and the hemoglobin (Hb) concentration of tumours was estimated. Results: We observed significant increase of the number of new vessels in mice fed LA in 3-day tumor angiogenesis tests. Tumors of LA fed mice presented, 14 days after cells grafting, significantly higher Hb content. Also, tumors excised from LA fed mice weighted significantly more than in controls. Conclusion: Stimulation of tumour growth by LA may be connected with pro-angiogenic activity of this substance.